A Botanical Inventory of Tropical Flowering Plants in Curug Lawe Waterfall, Semarang, Central Java: Inventarisasi Botani Tumbuhan Berbunga Tropis di Air Terjun Curug Lawe, Semarang, Jawa Tengah - Nofitasari, Titin Ayuk; Maharani, Riztiyana; Nafisah, Kharirotun; Prasastri, Ratri; Kusumarini, Niken (BIO-EDU: Jurnal Pendidikan Biologi, 2025)
Indonesia is one of the countries located on the equator and has a tropical climate. Due to this climate, Indonesia has a high level of flora and fauna. One of them is the diversity of tropical flowers and plants. One of the most diverse tropical flower habitats in Indonesia is Curug Lawe in Semarang Regency, Central Java. This study aims to determine the diversity of tropical flowering plants in the Curug Lawe waterfall area, Semarang Regency. The method used in this study is descriptive exploratory with a qualitative approach. The results of observations of tropical flowering plants in the Curug Lawe area obtained 17 families of Asteraceae, Heliconiaceae, Iridaceae, Commelinaceae, Araceae, Balsaminaceae, Costaceae, Verbenaceae, Gesneriaceae, Lamiaceae, Lythraceae, Amaranthaceae, Proteaceae, Rubiaceae, Malvaceae, Oxalidaceae, and Rosaceae. These results show the high diversity of tropical flowers in the Curug Lawe area because it has supportive environmental conditions. Tropical flowering plants have various benefits, including being used as medicines, ornamental plants, as cooking ingredients, anticancer, antioxidant, antibacterial, anti-inflammatory, antimicrobial, as insecticides, and industrial oils.